Melatonin and Angelman Syndrome: Implications and Mathematical Model of Diurnal Secretion - Justyna Paprocka; Marek Kijonka; Piotr Wojcieszek; Marcin Pęcka; Ewa Emich-Widera; Maria Sokół (International Journal of Endocrinology)
The main aim of the study was to compare the melatonin rhythms in subjects with Angelman syndrome (n=9) and in children with (n=80) and without (n=40) epilepsy (nonepileptic patients diagnosed with peripheral nerve palsies, myopathy, and back pain) using our mathematical model of melatonin circadian secretion. The characteristics describing the diurnal hormone secretion such as minimum melatonin concentration, release amplitude, phase shift of melatonin release, and sleep duration as well as the dim light melatonin onset (DLMO) of melatonin secretion and the γ shape parameter allow analyzing the fit and deducing about how much the measured melatonin profile differs from a physiological bell-shaped secretion. The estimated sleep duration and phase shift of melatonin release as well as the DMLO offsets at 25% and 50% relative thresholds are the key characteristic of Angelman syndrome children. As revealed from the γ shape parameter, the melatonin secretion profiles are disturbed in majority of the AG subjects revealing rather a triangular course instead of the bell-like one.